The problematic of the literary translation from Arabic to Spanish, study and analysis - Abbas, Mohammed Riyadh; Jasim, Reyadh Mahdi (Al-Adab Journal, 2022)
Literary translation is the most complex and difficult type among the other types of translation, mainly this is due to the complexity of the literary language itself, and therefore many problems often come along with the process of this translation. This research will present an analytical-contrastive study of the problems of literary translation from Arabic to Spanish, with examples of original texts in Arabic and their respective translations into Spanish. Through the linguistic analysis of translation errors and problems which is applied on our corpus, we intend at the end to extract practical considerations and conclusions to transgress these errors in the future works and participate in the efforts to establish a guideline for the literary translation from Arabic to Spanish.